Effects of a competitive wrestling season on body composition, strength, and power in National Collegiate Athletic Association division III college wrestlers - Schmidt, W. D.; Piencikowski, C. L.; Vandervest, R. E. (The Journal of Strength and Conditioning Research, 2005)
The purpose of this study was to investigate the effects of a competitive wrestling season on body composition, muscular strength, and muscular power in National Collegiate Athletic Association (NCAA) Division III college wrestlers. A total of 10 wrestlers were assessed throughout 2 consecutive wrestling seasons in late October, late January (midseason), and late March (postseason). Measurements included body weight, body composition (6-site skinfold), muscular strength (back squats and bench press), and muscular power (e.g., power cleans, vertical jump, seated medicine ball put). A repeated-measures analysis of variance (ANOVA) showed no significant changes in body weight, percentage of body fat, or fatfree mass (FFM) from pre- to mid- to postseason (body weight, 77.9 +/- 12.4, 75.7 +/- 11.0, and 79.9 +/- 12.8 kg; percentage of body fat, 11.6 +/- 3.9, 10.5 +/- 3.0, and 12.0 +/- 3.4; FFM, 68.5 +/- 8.7, 67.5 +/- 8.2, and 70.0 +/- 9.0 kg). A statistically significant main effect of time (p < 0.01) was observed for muscular strength, as both the back squat and bench press measures were lower at midseason (back squat, 150.8 +/- 25.2 kg; bench press, 98.3 +/- 25.4 kg) than at pre- and postseason (back squat, 157.9 +/- 25.5 and 161.4 +/- 25.6; bench press, 103.4 +/- 25.5 and 106.4 +/- 26.0). Muscular power did not change significantly throughout the wrestling season. These data indicate that Division III college wrestlers remain relatively weight stable with little change in body composition during a competitive wrestling season. While muscular power is apparently maintained, muscular strength may decline slightly. Our findings suggest that these wrestlers benefit from a training program that emphasizes in-season strength maintenance.